A Numerical Simulation Of Severe Cyclone Sidr-2007 - Sarkar, Nikhil Chandra; Islam, Anowarul; Debsarma, Sujit Kumar (GANIT: Journal of Bangladesh Mathematical Society, 2013)
The most severe tropical cyclones are formed over the Bay of Bengal because of its complex geometric structure and shallow coastal bathymetry. These natural disasters significantly impact our lives as well as the environment. To quantify the impact of such disasters, we analyzed data pertaining to the severe cyclone Sidr-2007, considering the cyclones duration and angle of land fall, as well as the bathymetry of the near-coastal zones. We propose a reliable hydrodynamic model to simulate the severity of such cyclones. The models reliability is verified by comparison of the numerical results with actual storm-surge data. Our model requires meteorological and hydrological inputs, including the time-dependent positions of the storm centre, the maximum wind radius, as well as pressure-drop and bathymetry data. The model results are in good agreement with the reported data. DOI: http://dx.doi.org/10.3329/ganit.v32i0.13645 GANIT J. Bangladesh Math. Soc. (ISSN 1606-3694) 32 (2012) 43-54